Survey of spontaneous pneumothoraces in the Royal Air Force - Cran, I. R. (1967)
Nine hundred and ninety-four cases of spontaneous pneumothorax which occurred in Royal Air Force personnel over a period of 22 years are reviewed. They are analysed in relation to age, side of occurrence, activity at the time of onset, and seasonal occurrence. Some clinical and radiological findings are presented and the incidence of recurrence is described (the possible association with emphysematous bullae is mentioned). Methods of treatment are discussed and those found most suitable for the special requirements of R.A.F. personnel are described. Spontaneous pneumothorax is thought to be more commonly diagnosed now and an increasing incidence in the R.A.F. in recent years is demonstrated.